Children with solid tumors treated in our centre - Sarbay, Hakan; Okumus, Mustafa; Sertbas, Idris; Hacisalihoglu, Uguray Payam; Atay, Avni; Malbora, Baris (International Journal of Contemporary Pediatrics, 2020)
Background: General characteristics and responses to treatment of patients with solid tumors were investigated. Methods: Patients treated with a diagnosis of solid tumors in the pediatric hematology and oncology clinic between March 2019 and June 2020 were included in the study. The gender, age, diagnosis, age of diagnosis, risk status, stage, treatment details, and treatment complications of the patients were evaluated. The risk status of the patients was determined according to the stage of each diagnosis, metastasis status and treatment protocol. It was noted whether the patients had undergone surgery or not, and patients who were in-operable were specified. Patients receiving radiotherapy were specified. The chemotherapeutic drugs given to the patients according to the treatment protocols were indicated one by one. Treatment complications or morbidity states were recorded. Results: Out of the 31 patients evaluated, 10 (32%) were female and 21 (68%) were male. The mean±SD age was 6.3±5.16 years. The youngest patient was 3 months old, and the oldest patient was 18 years old. The central nervous system was the most commonly affected area and 7 (22%) of the patients had various CNS tumors. The second most common malignancy is neuroblastoma; 4 patients (12%). Rhabdomyosarcoma and retinoblastoma were the third most common malignancy with 3 patients each. Surgical resection was performed in 19 (61%) patients. Radiotherapy was applied to 13 of the patients (41%). Conclusions: Early diagnosis and detection of the disease at low stage, complete tumor resection are important for the success of treatment.